Heterogeneous Users and the Peak Load Pricing Model - Jordan, W. John (Quarterly Journal of Economics, 1983)
The principal finding of this paper is that the conventional pricing solution for the peak load pricing problem must be modified to be applicable to a joint facility that is utilized by heterogeneous groups of users. The paper indicates how extending the conventional model through a multidimensional approach to capacity, accounting for its physical dimensions as well as its time dimension, will require specific capacity charges to users independent of the time of consumption. Any additional congestion charges levied will not perform the conventional role of covering replacement capacity costs, but will be used to reduce current congestion costs.